CHLOROGENIC ACID FROM SARGASSUM ILICIFOLIUM ATTENUATES CHEMOTHERAPYINDUCED NEPHROTOXICITY THROUGH SIRT1 ACTIVATION - CHANDUPATLA RAMYA; RAHUL INGLE; PATCHIGONDLA REENA SOWMYA; GURUSAMY MARIAPPAN (Asian Journal of Pharmaceutical and Clinical Research, 2026)
Objectives: The present study aimed to evaluate the nephroprotective potential of Sargassum ilicifolium extract against cyclophosphamide (CPM) drug-induced kidney injury using integrated in vitro, in silico, and in vivo approaches, with emphasis on sirtuin 1 (SIRT1)-mediated mechanisms. Methods: The ethanolic extract of S. ilicifolium was characterized using ultraviolet-visible spectroscopy, Fourier transform infrared, nuclear magnetic resonance, and liquid chromatography-mass spectrometry (LC-MS) analyses. Cytotoxicity and SIRT1 expression were assessed by SIRT1 assay in HK-2 cells, supported by molecular docking studies of chlorogenic acid (CGA) with SIRT1. Acute oral toxicity and nephroprotective efficacy were evaluated in cyclophosphamide-induced renal injury in rats through biochemical and histopathological analyses. Results: LC-MS analysis revealed diverse phytochemicals, with CGA identified as the major constituent (m/z 354.31, retention time 4.5 min). CGA exhibited low cytotoxicity (IC50=237.6 μg/mL) and significantly restored SIRT1 expression in HK-2 cells. Docking studies showed favorable binding with SIRT1 (–5.85 kcal/mol). In vivo, cyclophosphamide markedly elevated serum creatinine (1.57±0.085 mg/dL), uric acid (5.95±0.267 mg/dL), and urea (98.23±3.549 mg/dL), whereas treatment with S. ilicifolium (400 mg/kg) normalized these biomarkers (~0.56 mg/dL creatinine, ~2.0 mg/dL uric acid, ~28–29 mg/dL urea) and preserved renal histoarchitecture. Cyclophosphamide induced electrolyte imbalance and renal tubular dysfunction in rats, whereas treatment with S. ilicifolium extract restored sodium (144.57±3.459 mmol/L) and chloride (101.22±0.465 mmol/L) levels and shifted potassium and calcium closer to the normal range, indicating renoprotective activity. All data were tested for statistical significance at **p<0.01 and ***p<0.001 versus the negative control. Conclusion: S. ilicifolium extract exhibited significant nephroprotective activity through SIRT1 upregulation, biochemical normalization, and renal tissue preservation, supporting its potential as a natural therapeutic candidate for drug-induced kidney damage.